'As Efficient as a Factory': Architectural and Managerial Discourses on Government Office Buildings in Belgium, 1919–39. (2022) - Maele, Jens Van de
ABSTRACT: This article investigates the impact of managerial ideologies on projects for new governmental office buildings in Belgium in the 1920s and 1930s. Following the prewar publication of F. W. Taylor's 'scientific management' theories, the scientisation of office activities was propagated by efficiency experts throughout the western world. In Belgium, as in France, the work of the mining engineer Henri Fayol was particularly influential. According to Fayol, private and public bureaucracies had to follow identical managerial principles, notably that all employees were to observe one another as much as possible. These ideas of visibility overlapped with the emphasis on transparency and open planning coming from quite a different quarter, namely Le Corbusier, Hannes Meyer and other modernist architects in the 1920s and 1930s. Yet how Fayol's ideal was to be realised without compromising the traditional need for privacy for high-ranking office workers remained unresolved. The article explores the ideas of two crucial expert groups — architects and managerial experts — over these issues as they developed in Belgium in the inter-war years. In the 1920s, the mining engineer Max-Léo Gérard called for ministerial buildings that facilitated 'collaborative work' and the information scientist Paul Otlet advocated an ideal type of government offices based on an architectural diagram that facilitated mutual observation. In the 1930s, the architect Stanislas Jasinski proposed remodelling the centre of Brussels as a series of office blocks, in a design copied from Le Corbusier's cruciform skyscrapers in the Plan Voisin. Such ideas received official endorsement with the Royal Commissariat for Administrative Reform under Louis Camu, which proposed to strengthen the societal role of governmental bureaucracy by rehousing the civil service in an enormous office complex close to the parliament. Contrasting with the idealism of these unrealised plans was one of the few government projects actually built, the Ministry of Science and Arts headquarters designed in 1929 by the in-house architect Georges Hano.